Strategi dan Tantangan dalam Meningkatkan Cakupan Vaksinasi COVID-19 untuk Herd Immunity - Emilia Arina (Jurnal Medika Hutama, 2021)
Several countries have made so many interventions for tackling COVID-19 pandemic and one of them is the implementation of vaccination programme. The vaccination program is performed to reduce transmission rates, reduce mortality, break the chain and achieve herd immunity. Herd immunity can be achieved if vaccionation coverage is 67%-80%. This study aims to analyze challenges and barriers in Covid-19 vaccination program across the world. The study design used was case study with a systematic review method with PRISMA guideline. The result of this study have found several things which become challenges in the implementation of Covid-19 vaccination, there are hesitation and willingness to be vaccinated, production capacity, vaccination stock and fair allocation for all individuals. Based on this analysis we found some strategy to overcoming this issue, that is targeted vaccination campaign and encourage domestic pharmaceutical industry to be able to produce their own vaccines by collaborating with each other domestic pharmaceutical industry or collaborating with foreign pharmaceutical industries.